Exploring Student’s perception using Tiktok application in English learning - Muhamad Fahmi Rizal; Aureline Ninda Restu Winiharto (JoMMiT, 2025)
Social media sites like TikTok have become importantresources for language acquisition in the digital age,particularly for English language learners. This studyinvestigates junior high school students' opinions about usingTikTok as a tool to improve their English speaking abilities.Key themes like improved speaking fluency, vocabularygrowth, accent awareness, and enhanced self-confidence areidentified by the study using qualitative approaches that includesemi-structured interviews with two participants. Results showthat students regularly copy TikTok creators, take thoughtfulnotes, and choose content that reflects their interests, all ofwhich lead to more individualized and motivated languagelearning. The study also emphasizes how TikTok promotesinformal learning environments and self-regulated learningtechniques. These observations highlight TikTok's potential asan additional language-learning tool that encouragesengagement, exposure to real language, and digital literacy.Despite the study's sample size constraints, it provides strongevidence that TikTok can be an effective teaching tool forhelping young learners improve their English speaking abilities.